Hydrothermal carbonization of medical wastes and lignocellulosic biomass for solid fuel production from lab-scale to pilot-scale. (1st January 2017) - Shen, Yafei; Yu, Shili; Ge, Shun; Chen, Xingming; Ge, Xinlei; Chen, Mindong
Abstract: An alternative way has been proposed for the PVC-containing medical wastes valorization by co-hydrothermal carbonization (HTC) with lignocellulosic biomass. The organic-Cl in PVC can be converted to the inorganic-Cl via hydrolysis, defunctionalization, recondensation, and aromatization in the HTC process. Followed by the washing process with the condensed water, the inorganic-Cl with high water-solubility could be removed from the solid products (i.e. hydrochar). Lignin as a biomass component can significantly improve the dechlorination efficiency of PVC in the HTC process. Here, the dechlorination performance of lignocellulosic components is given as the following order: lignin > cellulose > hemicellulose. In addition, lignin can adjust the particle sizes of solid products by inhibiting the agglomeration in the order of lignin > hemicellulose > cellulose. In the pilot-scale HTC process, the addition of woodchips improves the dechlorination efficiency of hospital wastes (HW). The hydrochar particles with low-chlorine content and higher heating value could be used as a clean coal-alternative fuel. Graphical abstract: Highlights: An alternative method has been proposed for converting PVC wastes to energy. Dechlorination efficiency was enhanced by co-HTC with lignocellulosic biomass. Organic chlorine was transformed into the inorganic chlorine via the HTC process. The dechlorination performance of lignocellulose was given: lignin > cellulose > hemicellulose. Lignin can adjust the particle sizes of hydrochars by inhibiting the agglomeration.